125k views
1 vote
Zacharias is using the quadratic formula to solve the equation 0 = –2x2 + 5x – 3. He begins by substituting as shown. Quadratic formula: x = StartFraction negative b plus or minus StartRoot b squared minus 4 a c EndRoot Over 2 a EndFraction Substitution: x = StartFraction negative 5 plus or minus StartRoot 5 squared minus 4(2)(negative 3) EndRoot Over 2(negative 2) EndFraction What error did Zacharias make? The –5 should be 5. The 52 should be –52. The 2 in the numerator should be –2. The 2 in the denominator should be –2

User Kalthir
by
5.6k points

2 Answers

3 votes

Answer: d on edge2020

Step-by-step explanation: no cap

User Sholom
by
5.4k points
3 votes

Answer:

The 2 in the numerator should be –2

Explanation:

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


-2x^(2) +5x-3=0

so


a=-2\\b=5\\c=-3

substitute in the formula


x=\frac{-(5)(+/-)\sqrt{5^(2)-4(-2)(-3)}} {2(-2)}


x=\frac{-5(+/-)√(25-24)} {-4}


x=\frac{-5(+/-)1} {-4}


x=\frac{-5(+)1} {-4}=1


x=\frac{-5(-)1} {-4}=1.5

therefore

The 2 in the numerator should be –2

User Maggon
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.